A de novo triplication on 2q22.3 including the entire ZEB2 gene associated with global developmental delay, multiple congenital anomalies and behavioral abnormalities. Issue 1 (December 2015) - Yuan, Haiming; Zhang, Lina; Chen, Mengfan; Zhu, Junping; Meng, Zhe; Liang, Liyang
Abstract Background Mowat-Wilson syndrome (MWS) is a genetic condition characterized by distinctive facial features, moderate to severe intellectual disability, developmental delay and multiple congenital anomalies. MWS is caused by heterozygous mutations or deletions of theZEB2 gene located on chromosome 2q22.3. At present, over 190 cases with mutations and deletions involving theZEB2 gene have been reported, but triplication or duplication of reciprocal region of Mowat-Wilson syndrome has never been reported. Case Presentation Here we report a 2-year-2-month-old boy carrying ade novo 2.9 Mb complex copy number gain at 2q22.3 involving triplication ofZEB2 gene. The boy is characterized by intrauterine growth retardation, hypotonia, cognitive impairment, multiple congenital anomalies and behavioral abnormalities. Conclusion This case provides evidence that triplication ofZEB2 gene may be clinical significance andZEB2 gene is likely to be a dosage sensitive gene.